MENIMBANG GAGASAN MUSYAWARAH DALAM PEMILU NASIONAL DI PAPUA - Azim, Muhammad Fauzan; Siregar, Sahnan Sahuri (Turast: Jurnal Penelitian dan Pengabdian, 2014)
The system of National Election which based on the principle of one man one vote one value aims to ensurethe sovereignty of the people through free suffrage and equal, in accordance with the supremacy of law. Thisprinciple does not apply to traditional Indonesian society, especially in Papua, because in this society theelection uses acclamation or better known as Noken. The practice of election by acclamation first acknowledged constitutionally by the Court of Constitution (MK) through  Decision with number 47-81 / PHPU.A-VI/ 2009. Substantively, Noken has turned the idea of deliberative democracy and able to realize the people’ssovereignty for indigenous peoples.